The Socio-Political Crisis in the Northwest and Southwest Regions of Cameroon : Assessing the Economic and Social Impacts - World Bank (World Bank, Washington, DC, 2021)
This study assesses the impact of the crisis on economic and social outcomes in Cameroon’s Northwest and Southwest regions as of 2019. Conflicts destroy tangible and intangible assets and strain surrounding areas, and subnational conflicts leave deep scars on a country’s social fabric, culture, and collective memories. The NWSW crisis is a particularly poignant example of this, as it has directly targeted official symbols of the state, including schools and courts of law, and the resulting large-scale displacement has had secondary impacts on neighboring regions and at the national level. As of the end of 2019, the conflict was still active, and some longer-term outcomes and political, social, security, and institutional impacts were not yet observable beyond anecdotal evidence. The ongoing crisis, combined with the COVID-19 pandemic, has kept the two regions largely inaccessible. This has complicated data collection, as well as efforts to generate a more detailed understanding of conflict dynamics and actors. Given these constraints, this study has pursued a pragmatic strategy of analyzing pertinent issues in a systematic manner and relying on available information from a range of sources, including national and local governments, humanitarian assessments, existing surveys, press and newspaper articles, key stakeholder interviews, and remote sensing to gauge the impact of the ongoing crisis. Because no primary data collection has been carried out, the study does not measure the impact as of a specific date in 2019. Rather, it has tried to identify the most up-to-date and relevant sources to illustrate the impact, including the analysis of satellite images.